Safety Evaluation of a Novel Strain of Bacteroides fragilis - Wang, Ye; Deng, Huimin; Li, Zhengchao; Tan, Yafang; Han, Yanping; Wang, Xiaoyi; Du, Zongmin; Liu, Yangyang; Yang, Ruifu; Bai, Yang; Bi, Yujing; Zhi, Fachao (Frontiers in Microbiology, 2017)
Commensal non-toxigenic Bacteroides fragilis confers powerful health benefits to the host, and has recently been identified as a promising probiotic candidate. We previously isolated B. fragilis strain ZY-312 and identified it as a novel strain based on 16S rRNA sequencing and morphological analyses. We also determined that ZY-312 displayed desirable probiotic properties, including tolerance to simulated digestive fluid, adherence, and in vitro safety. In this study, we aim to investigate whether ZY-312 meets the safety criteria required for probiotic bacteria through comprehensive and systematic evaluation. Consequently, the fatty acid profile, metabolite production, and biochemical activity of strain ZY-312 were found to closely resemble descriptions of B. fragilis in Bergey’s manual. Taxonomic identification of strain ZY-312 based on whole genome sequencing indicated that ZY-312 and ATCC 25285 showed 99.99% similarity. The 33 putative virulence-associated factors identified in ZY-312 mainly encoded structural proteins and proteins with physiological activity, while the lack of bft indicated that ZY-312 was non-toxigenic. In vivo safety was proven in both normal and immune-deficient mice. The 11 identified antibiotic resistance genes were located on the chromosome rather than on a plasmid, ruling out the risk of plasmid-mediated transfer of antibiotic resistance. In vitro, ZY-312 showed resistance to cefepime, kanamycin, and streptomycin. Finally, and notably, ZY-312 exhibited high genetic stability after 100 passages in vitro. This study supplements the foundation work on the safety evaluation of ZY-312, and contributes to the development of the first probiotic representative from the dominant Bacteroidetes phylum.